Workshop pembuatan aplikasi arsip elektronik - Lalu Muhammad Fauzi; Muhammad Gazali; Husnul Mukti; Nila Hayati; Baiq Fitri Rahmawati (Universitas Hamzanwadi, 2022)
Each archive can help one's memory of a particular manuscript as an information center. As a source of documentation, archives can be used by organizational leaders in making appropriate decisions regarding the problems at hand as an official proof of responsibility for the administration's administration. Teachers are not only required to march in understanding the subject matter, but teachers must also be able to archive important documents as part of implementing learning. It is considered essential to provide workshops or training in electronic archive applications. The workshop was carried out for one whole day with details of the provision of materials, the practice of making electronic applications, and mentoring of participants after the workshop activities were completed. The workshop will be held on Saturday, August 28, 2021, at SDN 4 Perigi. The results of the workshop provide an illustration that participants have been able to create electronic archive applications using the Auto Play Media Studio 8.0 application